Reframing Gold Mining in Mount Tumpang Pitu: Uncovering Community Complexity in the Flow of Risk - Tiara Yulita Sari; Septian Rahmat Purnomo; Agung Dharma Yuda Adi Ramadhan; Nurina Adi Paramitha (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2023)
In addition to being known through the beauty of its landscape, Banyuwangi Regency is also known as one of the largest gold-producing areas in Indonesia. The gold is none other than the result of mining activities by the private sector which is directly supported by the local government. The gold mine is located on Mount Tumpang Pitu in Sumberagung Village, Pesanggaran District. Mining activities carried out have had various impacts on the surrounding community. One of the impacts that can be seen is the increase in income as well as the welfare of residents around the mine. However, there are also potential risks that are ready to threaten the community itself. Therefore, this research aims to reveal the complexity of the community through the flow of risk in the face of mining activities carried out at Mount Tumpang Pitu through the perspective of the risk community proposed by Ulrich Beck. This research is qualitative research with a phenomenological approach. The results showed that mining in Mount Tumpang Pitu, in addition to benefiting the private sector as mining managers, also contributed to advancing the welfare of the surrounding community. However, on the other hand, some risks have occurred such as mud flooding in coastal areas. This research concludes that mining risk is a boomerang effect of modernity which then leads the community to individual reflectivity. Therefore, it is necessary to increase the prudence of attitudes and actions by all parties involved with mining in Mount Tumpang Pitu.